2018
DOI: 10.1038/s41477-018-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and spatial restriction of Polycomb activity by plant histone demethylases

Abstract: Targeted changes in chromatin state at thousands of genes are central to eukaryotic development. RELATIVE OF EARLY FLOWERING 6 (REF6) is a Jumonji-type histone demethylase that counteracts Polycomb repressive complex 2 (PRC2)-mediated gene silencing in plants and was reported to select its binding sites in a direct, sequence-specific manner. Here we show that REF6 and its two close paralogues determine spatial 'boundaries' of the repressive histone H3K27me3 mark in the genome and control the tissue-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 63 publications
7
99
0
1
Order By: Relevance
“…In Arabidopsis, three partially redundant homologs CURLY LEAF (CLF), MEDEA (MEA), and SWINGER (SWN) encode the catalytic subunit of the PRC2 histone methyltransferase (HMT), while EMBRYONIC FLOWER2 (EMF2) encodes a second core PRC2 component (Schmitges et al, 2011;Müller-Xing et al, 2014a). In contrast, RELATIVE OF EARLY FLOWERING6 (REF6) and its two close paralogs, EARLY FLOWERING6 and JMJ13, are three partially redundant H3K27me3 demethylases (erasers) with important functions in reprogramming during plant development ( Table 2; Yan et al, 2018).…”
Section: Epigenetic Regulation Of Dnrr By the Repressive Mark H3k27me3mentioning
confidence: 99%
“…In Arabidopsis, three partially redundant homologs CURLY LEAF (CLF), MEDEA (MEA), and SWINGER (SWN) encode the catalytic subunit of the PRC2 histone methyltransferase (HMT), while EMBRYONIC FLOWER2 (EMF2) encodes a second core PRC2 component (Schmitges et al, 2011;Müller-Xing et al, 2014a). In contrast, RELATIVE OF EARLY FLOWERING6 (REF6) and its two close paralogs, EARLY FLOWERING6 and JMJ13, are three partially redundant H3K27me3 demethylases (erasers) with important functions in reprogramming during plant development ( Table 2; Yan et al, 2018).…”
Section: Epigenetic Regulation Of Dnrr By the Repressive Mark H3k27me3mentioning
confidence: 99%
“…Our discovery of CUC1-1 methylation in the methylomes of Arabidopsis explains a previous report that no REF6 binding is detected when using a CUC1-1 substrate 13 . Recently, it is also reported that other factors, such as chromosome states, binding partners, the number of binding motifs, and even dependence on transcription factors, may influence the recognition by REF6 in vivo [40][41][42][43][44] . Take the case of CTCTGYTY-motif clusters, due to the high affinity from cooperativity, REF6 can tolerate sequence variation in the CTCTGYTY motif and thus might bind many kinds of motifs.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are thought to mediate the temporal and spatial de-repression of genes necessary for a wide range of plant processes such as flowering, hormone signaling, and the control of the circadian clock. Inactivation of REF6 results in the ectopic accumulation of H3K27me3 at hundreds of loci, many of them involved in developmental patterning and environmental responses (Lu et al, 2011;Yan et al, 2018). It has been proposed that REF6 is recruited to a specific sequence motif through its zinc-finger domain (Cui et al, 2016;Lu et al, 2011); however, others have shown that it is also recruited by specific interactions with transcription factors (Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of REF6 results in the ectopic accumulation of H3K27me3 at hundreds of loci, many of them involved in developmental patterning and environmental responses (Lu et al, 2011;Yan et al, 2018). It has been proposed that REF6 is recruited to a specific sequence motif through its zinc-finger domain (Cui et al, 2016;Lu et al, 2011); however, others have shown that it is also recruited by specific interactions with transcription factors (Yan et al, 2018). Moreover, it has been shown that the affinity of REF6 to chromatin is hindered by DNA methylation, which could explain why its activity is primarily found at euchromatic loci (Qiu et al 2019).…”
Section: Introductionmentioning
confidence: 99%